Severity and Mortality of Covid-19 in Patients with Diabetes Mellitus - Malik Fayyaz Hussain Awan, Sarwar Malik, Fatima Qayyum, Qaisar Ali, Asad Munir, Aiman Altaf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Covid-19 infection appeared as rapidly spreading cases of acute respiratory disease in Wuhan city of China that became pandemic. It was brought to the notice of WHO on December 31, 2019. Diabetes mellitus is one of the biggest health problems and fast growing emergencies of the 21st century. Diabetic patients with who got infected with Covid-19 have more chance of in hospital treatment need, intensive care unit care requirement, intubation and death. Objective: The objective of this study was to know the severity and mortality of covid-19 in patients with diabetes mellitus. Study Design: This was a descriptive case series study. Study Setting: It was done in the Covid-19 isolation and ICU unit of Ayub Teaching Hospital Abbottabad from May 2020 to October 2021. Methods: Using non-probability consecutive sampling, 189 diabetic patients were enrolled. Sample included all covid-19 patients having diabetes that received indoor treatment during this period. All patients from both genders with age > 18 years were included. Patients with malignancy or on immunosuppressants for more than 1 month were excluded. Patients who were maintaining oxygen saturation at room air/facemask/nasal prongs were labelled as having non-severe disease while patient who needed CPAP or assisted ventilation were labelled as having severe covid-19 disease. All patients who died during admission were documented as covid-19 related mortality. Patients were labelled as diabetic who were known diabetic and taking diabetes treatment. Data was collected on a structured pro forma. Statistical program SPSS version 16.0 was used for the analysis of data. Results: In this study, mean age was 61.29 ± 11.73 years. There were 40.2% male and 59.8% female patients. 86.2% patients were not-vaccinated, 3.7% patients were partially vaccinated and 10.1% patients were fully vaccinated. Hypertension was most common comorbidity (42.3%) and only CKD was significantly associated with increased mortality. 43.92%patients had non-severe illness while 56.08% patients had severe illness. The overall mortality of illness was 48.15% while it was 84.9% in patients with severe illness.